A lawful history: judicial ordines, the ius commune and virtuous litigation in Norman Sicily - Byrne, P (Cambridge University Press, 2019)
This article considers the developing role of the ius commune in twelfth-century Sicily through an examination of the text known as the Historia de Regno Sicilie. The text, a narrative history, has long been mined by historians as a document of mid-century political crisis in the kingdom. This article, however, argues that the Historia should be interpreted through a legal frame: its purpose can only be understood when it is read against twelfthcentury ordines iudiciarii. The Historia seeks to identify a set of normative rules for judicial conduct, invoking a specific and technical vocabulary. As such, it can be read as a document of the reception of Roman law in Sicily. The article then discusses how the Historia stands in relation to other evidence for the development of ius commune jurisprudence in the Norman regno, and the ways in which the text may provide a distorted picture of legal practice. Finally, it considers why an argument about procedural law should have been made in the form of a narrative history, and what this might suggest about broader trends in twelfthcentury thought.